Conditional cash transfers (cct) in Latin America: Analyzing their potentials and challenges special reference to the Argentine Republic - Rezzoagli, Luciano Carlos (2016)
Conditional cash transfers as a financial instrument for resource allocation directed towards vulnerable social sectors, was widely used since the 90s until today, both in Latin America and developing countries in other continents and even some developed countries. However, the problems and challenges that come with such interventions require a detailed analysis of opportunity, implementation, evaluation and control to determine its legitimacy, potentials and challenges. It is a qualitative, non - experimental, logical - descriptive and analytical study.